KEPENTINGAN INDONESIA BERPARTISIPASI DALAM ASEAN COAST GUARD FORUM (ACGF) - Padmarini, Aatifah Dhiyan; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia as one of the archipelagic countries in Southeast Asia that has various maritime security dynamics has actively participated in maritime cooperation between coast guards called the ASEAN Coast Guard Forum (ACGF). Therefore, this paper will examine the factors driving Indonesia's participation in the ACGF represented by Bakamla RI despite being active in other maritime security cooperation. To answer this question, we will use a qualitative method with data collection techniques through document analysis sourced from Bakamla RI, and supported by books, journals, articles, and other official documents. This research also uses the perspective of Neo-realism with the theory of Maritime Security and the concept of National Interest, which is related to defense interests. The results of this paper show that Indonesia's interest in participating in the ACGF is due to maritime defense interests due to maritime security threats such as transnational crimes that appear in Indonesian waters and maritime defense as one of the pillars in Indonesia's vision, namely the vision of a world maritime axis. Keywords: ASEAN Coast Guard Forum, Maritime Security, Interests, Bakamla RI, Participation.